The Determinant of Commercial Banks' Interest Margin in Indonesia: An Analysis of Fixed Effect Panel Regression - Raharjo, Pamuji Gesang; Hakim, Dedi Budiman; Manurung, Adler Hayman; Maulana, Tubagus N.A. (International Journal of Economics and Financial Issues, 2014)
The purpose of this research is to study and analyze the determinant factors of commercial banks’ interest margin in Indonesia, both internal factors (bank specific factors) and external factors. Internal factors are selected under this study consists of several aspects such as growth of the bank's assets, profitability, efficiency, capital adequacy, liquidity, and risk, meanwhile external factors are market power, inflation, and interest rates. Several variables have been used in previous studies to be used as a proxy. The study applied fixed effects on a panel data regression model to a panel of Indonesian commercial banks that covers the period 2008 – 2012. The results show consistent findings from previous studies. The net interest margin of Indonesian commercial banks are affected by the entire internal variables on a different level of significance, meanwhile inflation is the only external factors that affects on interest margins significantly at 5% level. Keywords: net interest margin; commercial bank; panel data JEL Classifications: C23; G21; L11 <!--[endif] -->